Review of the ‘Xylaplothrips-complex’ (Thysanoptera, Phlaeothripidae) from East Asia - Okajima, Shûji; Masumoto, Masami (Zootaxa, 2025)
The East Asian genera and species, most of which have previously been classified into two polyphyletic genera, Mesandrothrips and Xylaplothrips of the tribe Haplothripini, are considered systematically. Six genera with 54 species are recognized from East Asia between Southeast Asia and Japan, of which four genera and 42 species are newly described. Habrandrothrips gen. nov. comprises two species: H. phuketanus sp. nov. and H. sulawesianus sp. nov. Leptandrothrips gen. nov. comprises six species: L. indosinae sp. nov., L. inexpectus sp. nov., L. nigrescens sp. nov., L. robustus comb. nov., L. semiflavus comb. nov. and L. zelkovae comb. nov. Mesandrothrips comprises eight species: M. brevisetis sp. nov., M. crassicornis sp. nov., M. eximius sp. nov., M. flavitibia, M. ichikaianus sp. nov., M. inquilinus, M. inquinatus and M. subterraneus. Neandrothrips gen. nov. comprises 28 species: N. acutisetis comb. nov., N. agkoae sp. nov., N. andromorphus sp. nov., N. apoae sp. nov., N. balianus sp. nov., N. bamboosae comb. nov., N. bogoriensis comb. nov., N. boninae sp. nov., N. dentipes sp. nov., N. dubius comb. nov., N. ilomavisae sp. nov., N. inermis sp. nov., N. japonicus sp. nov., N. kadazani sp. nov., N. kundasangi sp. nov., N. kutae sp. nov., N. ommatocellus sp. nov., N. pahangi sp. nov., N. pictipes comb. nov., N. rangi sp. nov., N. simulans sp. nov., N. spinipes sp. nov., N. subinermis sp. nov., N. tabananensis sp. nov., N. taiwanus sp. nov., N. tonesai sp. nov., N. uniconus sp. nov., N. uniformis sp. nov. and N. yangmingshanae sp. nov. Xylaplothrips comprises one species: X. togashii. Xyphandrothrips gen. nov. comprises nine species: X. amamianus sp. nov., X. cinctus sp. nov., X. conjunctus sp. nov., X. formosae sp. nov., X. karaentae sp. nov., X. megacephalus sp. nov., X. pallens sp. nov., X. septemfidus sp. nov. and X. vietnamicus sp. nov. The relationships of these six genera are considered, and five keys are provided for these genera excluding Xylaplothrips. The following 16 species known from the regions other than East Asia are transferred to Neandrothrips from Mesandrothrips or Xylaplothrips: N. austrosteensis comb. nov., N. caliginosus comb. nov., N. clavipes comb. nov., N. debilis comb. nov., N. emineus comb. nov., N. flavus comb. nov., N. googongi comb. nov., N. kurandae comb. nov., N. lamingtoni comb. nov., N. ligs comb. nov., N. mimus comb. nov., N. montanus comb. nov., N. oleariae comb. nov., N. pusillus comb. nov., N. reedi comb. nov. and N. tener comb. nov.